Project-based incident rate based on weighted average method / Khairul Anwar Rasmani ...[et al.] - Rasmani, Khairul Anwar; Mohamed Yusof, Noreha; Amit, Norani; Mohd Lip, Norliana; Ramli, Hazwani; Rosli, Nur Nadiah; Rusli, Anis Dayana (Penerbitan UiTM, 2021)
The incident rate has been widely used to indicate safety performance. The incident rate of a company can be compared with the national or international incident rate within similar industry or among different types of industries. The comparison is particularly very useful as a safety benchmark to gauge performance with other companies in the same business area. However, many existing methods produce the annual incident rate, which has been formulated on an annual basis. This will lead to incompatibility of the method used in calculating the incident rate for a project that runs for a specific period. This is because the annual incident rate does not consider the duration of the project; it becomes less meaningful in indicating the safety performance of project-based activities such as those in construction industries. The proposed method which is Project-Based Incident Rate (PIR) is found to be able to reflect the actual situation of project-based companies better than the existing annual incident rate method, and it is also can be expressed both on a monthly and yearly basis.